Expecting Brexit - Swati Dhingra; Thomas Sampson (Center for Economic Studies and ifo Institute (CESifo), 2022)
The Brexit vote precipitated the unravelling of the UK's membership of the world's deepest economic integration agreement. This paper reviews evidence on the realized economic effects of Brexit. The 2016 Brexit referendum changed expectations about future UK-EU relations. Studying its consequences provides new insights regarding the economic impacts of news and uncertainty shocks. Voting for Brexit had large negative effects on the UK economy between 2016 and 2019, leading to higher import and consumer prices, lower investment, and slower real wage and GDP growth. However, at the aggregate level, there was little or no trade diversion away from the EU, implying that many of the anticipated long-run effects of Brexit did not materialize before the new UK-EU trade relationship came into force in 2021.
Keywords: E22; E65; F13; F15; F16; F31; F40; 330; Brexit; trade policy; uncertainty; exchange rates